Social Anxiety in Children and Adolescents With Autism Spectrum Disorders Contribute to Impairments in Social Communication and Social Motivation - Briot, Kellen; Jean, François; Jouni, Ali; Geoffray, Marie-Maude; Ly-Le Moal, Myriam; Umbricht, Daniel; Chatham, Christopher; Murtagh, Lorraine; Delorme, Richard; Bouvard, Manuel; Leboyer, Marion; Amestoy, Anouck (Frontiers in Psychiatry, 2020)
Recognition of symptoms of Social anxiety (SA) may be difficult among individuals with Autism Spectrum Disorders (ASD) because of overlap between social anxiety and autistic symptomatology. The main aim of our study was thus to explore the association between symptoms of social anxiety and clinical characteristics of ASD in order to identify individuals, with specific clinical features, experiencing concomitant ASD and social anxiety disorder. We also described the prevalence of SA in a sample of children and adolescents with ASD. 79 children and adolescents with ASD (with and without intellectual disability) and 28-matched control participants were recruited in two French Expert Centers for ASD, coordinated by the Fundation FondaMental. Psychiatric comorbidities, anxiety disorders and depression were screened with standard tools (Liebowitz social anxiety scale, Hamilton Depression and Anxiety Rating Scale) and correlated to autistic features and social skills assessed with the social responsiveness scale 2 (SRS-2) and the repetitive behavior scale (RBS-R). We performed bivariate analysis between the social anxiety level and the scores measured with different clinical scales. We then adjusted the observed relationships with the alterations of SRS-2 and RBS-R scores. After adjustment, the level of social anxiety appeared as significantly associated with alterations in social reciprocity and particularly with the SRS-2 “social communication” and “social motivation” sub-scores, but not with RBS-R score. We confirm previous reports showing that individuals with ASD are at high risk for specific anxiety disorders. In particular, high levels of impairments in social motivation and social communication (SRS-2) are indicative of comorbid disorders namely, social anxiety and ASD. Our findings clearly inform diagnostic assessment in ASD and stress the need to take comorbid anxiety disorders into consideration to improve treatment of ASD. To further clarify the impact of social anxiety on social competences and socio-adaptive handicap, longitudinal studies and cluster analysis will be needed in the future.